Strategi Komunikasi BBPPMPV BMTI dalam Mensosialisasikan Adaptasi Penggunaan Energi Terbarukan : - - Mira Kumala; Santana, Septiawan; Wiwitan, Tresna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The dominant use of fossil energy in Indonesia, especially petroleum and coal, has resulted in its availability becoming increasingly depleted, so Renewable Energy (RE) is needed to anticipate this. The use of RE is the best alternative as an effort to reduce the use of fossil energy. The government must pay attention to this. To support the Government in implementing the conversion of fossil energy to RE, outreach to the public is needed. This research aims to find out the steps in planning a communication strategy in socializing the adaptation to the use of renewable energy carried out by Quality Assurance Development Center For Vocational Education in Mechanical and Industrial Engineering (BBPPMPV BMTI), there are three important elements in planning communication strategies, namely the application of the SMART formulation in determining communication targets (audience), selecting target groups and how to convey messages. The method used in this research is qualitative, data collection techniques are carried out through observation, interviews and literature studies. Research findings and results show that Indonesia needs socialization related to RE in the form of direct teaching which contains the practice of using, manufacturing or constructing RE Power Generation (PLET) devices that can be utilized by the community. Communication strategy carried out by BBPMPPV BMTI in Socializing Adaptation to the Use of RE through TET Training. The TET training conducted by BBPPMPV BMTI is a form of socialization in which there is direct teaching containing the practice of using, manufacturing or constructing RE Power Generation (PLET) devices that can be utilized by the community.